The impact of exercise environments on adolescents' cognitive and psychological outcomes: A randomised controlled trial. (July 2020) - Wade, Levi; Lubans, David R.; Smith, Jordan J.; Duncan, Mitch J.
Abstract: Exercise in natural environments can improve cognition, positive affect, and reduce psychological stress. However, it remains unclear whether these benefits are subject to a gradient effect, whereby more natural features confer greater cognitive and psychological benefits. This study examined the influence of the exercise environment (i.e., the degree of nature) on cognition, and psychological outcomes in a sample of adolescents (n = 90; mean age = 14.3 ±.05 years). Four groups were randomised to one of the following experimental conditions: a non-exercise indoor control, indoor exercise, park exercise, and exercise in a nature reserve. Participants' self-reported their stress, affect, and vitality and completed two measures of cognition ('Rapid Visual Information Processing' and 'Spatial Working Memory') immediately before and ~6 min after exercise. All exercise conditions participated in a group-based circuit lasting ~20 min, which included a mixture of aerobic and body-weight resistance activities. Linear mixed models were used to examine changes within and between groups. The indoor group increased sustained attention accuracy compared to the park group. There were no between-group differences in working memory. The indoor and nature groups increased cognitive arousal compared to control. The park group improved in state-level vitality compared to control. The mixed-results of this research do not support our 'nature gradient' hypothesis, whereby cognitive and psychological outcomes would improve in accordance with the degree of nature present in the exercise environment. Highlights: Improvements in sustained attention accuracy favoured indoor over park exercise. Park exercise resulted in improvements in state-level vitality. No evidence that exercise environment influences working memory. No conclusive nature gradient effects on cognitive and psychological outcomes.